TiO2 nanotubes co-modified by Ag/AgCl plasmonic photocatalyst and graphene and a comparison of their enhanced photocatalytic performance under ultraviolet and visible light. (25th July 2018) - An, Huiqin; Yan, Lin; Wang, Huizhen; Chang, Cheng; Li, Min; He, Xiaoling; Huang, Weiping
Abstract: Ag/AgCl-modified TiO2 nanotube photocatalysts (noted as Ag/AgCl/TiO2 nanotubes) are synthesized by the combine of deposition-precipitation and photoreduction methods firstly, and then reduced graphene oxide (rGO) is deposited on the Ag/AgCl/TiO2 nanotubes via a simple one-pot solvothermal method. TEM, HRTEM, XRD and UV–vis are utilized to characterize the morphology, microstructure, composition and optical property of the obtained samples. The photoactivities of samples are evaluated by the photodegradation of methyl orange under ultraviolet and visible light irradiation, respectively. The effects of contents of AgCl, Ag and rGO on the photocatalytic performance of Ag/AgCl/TiO2 nanotubes and rGO modified Ag/AgCl/TiO2 nanotubes are investigated, respectively, and their optimal contents are obtained. The results reveal that, after Ag/AgCl modification, the samples exhibit an absorption in visible region due to the surface plasmon resonance of metallic Ag nanoparticles. Besides that, the enhanced photocatalytic activities of Ag/AgCl/TiO2 nanotubes and rGO modified Ag/AgCl/TiO2 nanotubes samples are observed during ultraviolet and visible light irradiation. Based on the results, the different photocatalytic mechanisms under ultraviolet and visible light irradiation are proposed.